Multimodal Power Management Based on Decision Tree for Internet of Wearable Things Systems - Jaime Ortegón-Aguilar; Alejandro Castillo-Atoche; Guillermo Becerra-Nuñez; Johan Jair Estrada-López; Edith Osorio-de-la-Rosa; Roberto Carrasco-Alvarez; Asim Datta; Javier Vázquez-Castillo (Applied Sciences, 2023)
Precision medicine is now evolving to include internet-of-wearable-things (IoWT) applications. This trend requires the development of novel systems and digital signal processing algorithms to process large amounts of data in real time. However, performing continuous measurements and complex computational algorithms in IoWT systems demands more power consumption. A novel solution to this problem consists in developing energy-aware techniques based on low-power machine learning (ML) algorithms to efficiently manage energy consumption. This paper proposes a multimodal dynamic power management strategy (DPMS) based on the ML-decision tree algorithm to implement an autonomous IoWT system. The multimodal approach analyzes the supercapacitor storage level and the incoming biosignal statistics to efficiently manage the energy of the wearable device. A photoplethysmography (PPG) sensing prototype was developed to evaluate the proposed ML-DPMS programmed in a Nordic nRF52840 processor. The experimental results demonstrate an IoWT system’s low consumption of 25.74 J, and a photovoltaic solar power generation capacity of 380 mW. The proposed ML-DPMS demonstrates a battery life extension of <semantics>3.87×</semantics>, i.e., 99.72 J of energy harvested, which represents the possibility to achieve at least <semantics>2.4×</semantics> more data transmissions, in comparison with the widely used uniform power management approach. In addition, when the supercapacitor’s energy is compromised, the decision tree technique achieves a good energy conservation balance consuming in the same period of time 39.6% less energy than the uniform power approach.